Komersialisasi Mobil Hibrida - Ibrahim, Irwan (Warta Penelitian Perhubungan, 2010)
NawadmJS hybrid vehicles become an interesting subject of discussion in relfltion with oil fucl amservationand air qualihJ Hybride car is considered suitable w cope with oil resenie depletion as 11~ll asto reduce exhaust emission of motor iielzic/es. All cnr mmwfncturers tnj to introduce their productswhich are excellent in technology nnd cowpetzmie in price. Howe1¥?r, due to tedznologtj embedded inhybrid car, demand on new nnd mre nmterinls is increasing. Plug-in hybrid which is more popularmay cause increase of pollution around the power plant area. T77ese matters also need appropriateattention.Hybrid cars are already introduced in Jakarta. Public interest is still 1'1eflj law due to limited informationon tl7e admntnges of lzybrid technology, m1d of course beer.use of lzigher piice of t/ze mr. Incentivesare necessary especinlly for tlie user of l1ybrid rnr in densely papulnted cities.Keywords: hybrid, electric motor, batten}